Ascertainment of myotonic dystrophy through cataract by selective screening. Issue 7 (July 1995) - Kidd, A; Turnpenny, P; Kelly, K; Clark, C; Church, W; Hutchinson, C; Dean, J C; Haites, N E
Abstract : Myotonic dystrophy (DM) almost always results from the expansion of an unstable (CTG)n repeat. The mutation can be detected directly. Affected patients with cataracts may have minimal additional signs of the disorder, but all are at risk of life threatening complications. We have studied the efficacy of detecting new families with myotonic dystrophy by selectively screening cataract patients. Selection criteria were: age under 60 with no obvious precipitating factor (except non-insulin dependent diabetes mellitus (NIDDM)); patients of any age with other signs suggestive of myotonic dystrophy detected by the ophthalmologist. Ninety-six patients were tested prospectively; 17 others under 55 were screened retrospectively. All patients were counselled by a clinical geneticist before testing. The patients' DNA was analysed using the DNA probe/restriction enzyme combinations GB2.6/EcoRI, KB1.4/BglI and polymerase chain reaction (PCR). Six patients have been found to have a mutation, three (3.1%) in the prospective group and three (17.6%) in the retrospective group. Three of these patients had minimal myotonic dystrophy and three had classical DM.